Scope of Development of Vaccine against Antibiotic Resistant Klebsiella pneumoniae: Current Perspective (Bangladesh Journal of Medical Microbiology, 2023)
Abstract Not AvailableBangladesh Journal of Medical Microbiology, January 2023;17(1):1-2